Coastal Hazard Modeling from Radar Data - Marghany, Maged; Mansor, Shattri (Universiti Putra Malaysia Press, 2000)
The effects of wave force or the effects of the coastal engineering structures induce coastal hazards such as erosion. Coastal engineering structures such as jetties could trap a sediment transport along the coastline. This could induce erosion in the downstream. The aim of this study is to model the effects of shoreline changes to jetties located along coastal water of Chendering, Malaysia. The numerical model will be based on the change of wave spectra extracted from ERS-I data. For this purpose, two-dimensional Fourier Transform was applied on window size of 200 x 200. The quasi-linear model was used to model significant wave height. The significant wave height was used to model the volume of sediment transport and shoreline evaluation along jetties. The result shows that the erosion occurred in the south of Chendering with rate of change of 4 m/month. The prediction shows that the rate of erosion would increase within 10 years. This study shows the location of jetty decreases the rate of sediment transport along the south of Chendering. It can be said that ERS-l data are able to predict shoreline evaluation along the coastal structures. The jetty induced an equilibrium beach profile along jetty. This is due to that jetties-trap sediment in the north of Chendering, which lead to erosion in the south of Chendering.